2020
DOI: 10.1002/cbf.3520
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic gene RGC‐32 is a direct target of miR‐26b and facilitates tongue squamous cell carcinoma aggressiveness through EMT and PI3K/AKT signalling

Abstract: Growing data have recognized the significance of Response Gene to Complement (RGC)-32 in numerous tumour developments. Notwithstanding, the functional role and underlying mechanism of it in tongue squamous cell carcinoma (TSCC) remain enigmatic. Here, to identify the impact of RGC-32 in TSCC, its expression in multiple TSCC cells was measured and loss-of-function experiments in cell lines were performed to illuminate the function of it induced TSCC progression, via si-RNA knockdown, CCK-8, colony formation, wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…An aberrantly activated or inactivated PI3K/ AKT signaling pathway has been identified in a variety of human diseases (18). Additionally, researches have shown that the PI3K/AKT signaling pathway is involved in controlling proliferation, apoptosis, and autophagy of RGCs (19)(20)(21). Notably, the PI3K/AKT signaling pathway plays an important role in preventing glaucomatous injury-induced loss of RGCs (22).…”
Section: Original Articlementioning
confidence: 99%
“…An aberrantly activated or inactivated PI3K/ AKT signaling pathway has been identified in a variety of human diseases (18). Additionally, researches have shown that the PI3K/AKT signaling pathway is involved in controlling proliferation, apoptosis, and autophagy of RGCs (19)(20)(21). Notably, the PI3K/AKT signaling pathway plays an important role in preventing glaucomatous injury-induced loss of RGCs (22).…”
Section: Original Articlementioning
confidence: 99%
“…Over several decades, PI3K/AKT pathway in TSCC has attracted a lot of attention from oncology researchers. For instance, it has been shown that the activation of PI3K/AKT signaling facilitates TSCC progression [25]; furthermore, the activation of the PI3K/AKT pathway is able to promote proliferation, migration, and invasion but inhibit apoptosis in TSCC cells [26]. Importantly, previous studies have proposed that TRPC1 is able to modulate PI3K/AKT pathway to regulate tumor progression in several malignancies [14,15,17].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of stimuli such as transforming growth factor [54], steroid hormones [55], and serum [56] are able to regulate the expression of RGCC. In tongue squamous cell carcinoma (TSCC), RGCC has a tumor-promoting effect, and its knock-down promotes cell apoptosis; furthermore, it can regulate the proliferation, trans-migration, and invasion of TSCC cells through EMT and PI3K/AKT signaling pathways [57]. In the developing mammalian neocortex, RGCC is exclusively expressed in neural stem cells (NSCs); its deficiency disrupts the cell cycle and spindle orientation of NSCs, which may lead to cell pre-differentiation and exhaustion of the NSCs pool [58].…”
Section: Discussionmentioning
confidence: 99%